The THE BIOPHILIC AND BIOCENTRIC DISCOURSE IN EDWARD ABBEY'S THE MONKEY WRENCH GANG - Walida, Badilatil; Tirmidi, Tirmidi (Jurnal Review Pendidikan dan Pengajaran, 2025)
This research aims to analyze ecologism discourse in Edward Abbey's novel through James Paul Gee's discourse analysis and Julia Kristeva's suprasegmental and intertextual approaches. The suprasegmental uses the psycholinguistic approach of Jan Renkema and Kristeva's intertextuality, provided by Gee's methodological tools. These approaches are used to know the novel's theme by Edward Abbey and to analyze how four characters from diverse backgrounds converge into their environmental commitments. Findings reveal that the theme was found to be a struggle to conserve the environment threatened by the dam's construction. Despite their different backgrounds, the four main characters share fundamental biophilic and biocentric traits that shape their ecological activism. Biophilic characteristics include protective love and territorial attachment, empathy toward nature and awe for natural wonders. In addition, their biocentric qualities manifest through voluntary simplicity, advocacy for nature's rights, and appreciation of natural aesthetics. Abbey's strategic narrative construction effectively communicates these ecological philosophies, ultimately influencing real-world environmental activism beyond the novel.